The MEDIATING ROLE OF SELF-EFFICACY IN THE RELATIONSHIP BETWEEN FAMILY ENVIRONMENT, MOTIVATION, AND ENTREPRENEURIAL INTENTION AMONG EMPLOYEES OF THE JAMBI HIGH PROSECUTOR’S OFFICE - Aurora, Claudia Ernestina; Dahmiri; Ekasari, Novita (Journal of Business Studies and Management Review, 2025)
The purpose of this study is to identify and analyze whether self-efficacy mediates the influence of the family environment and motivation on the entrepreneurial intention of employees at the High Prosecutor’s Office of Jambi. The population used in this study consists of all employees of the High Prosecutor’s Office of Jambi in 2024, totaling 224 individuals. Based on calculations using the Slovin method, the sample size for this study is 144 respondents. The data analysis technique employed is Partial Least Squares (PLS) analysis. Based on the research findings, it can be concluded that the family environment, motivation, and self-efficacy play very important roles in shaping the entrepreneurial intention of employees at the High Prosecutor’s Office of Jambi. The family environment was found to be in the “very good” category and serves as a strong supporting factor, in line with the high level of entrepreneurial motivation among employees, which is driven by the desire to improve welfare, independence, and self-actualization. In addition, self-efficacy was also categorized as “very good,” reflecting employees’ confidence in their ability to run a business. Entrepreneurial intention itself shows a positive tendency and falls into the “good” category. Empirically, the family environment and motivation have a positive and significant effect on entrepreneurial intention, both directly and indirectly through self-efficacy. Furthermore, self-efficacy has also been proven to have a positive and significant effect on entrepreneurial intention. These findings confirm that strong family support and high motivation enhance self-efficacy, which in turn strengthens the entrepreneurial intention of employees at the High Prosecutor’s Office of Jambi.